Improved electroluminescence of quantum dot light-emitting diodes enabled by a partial ligand exchange with benzenethiol. (9th May 2016) - Kim, Daekyoung; Fu, Yan; Kim, Jungwoo; Lee, Ki-heon; Kim, Hyoungsub; Yang, Heesun; Chae, Heeyeop
Abstract: In this study, benzenethiol ligands were applied to the surface of CdSe@ZnS core@shell quantum dots (QDs) and their effect on the performance of quantum dot light-emitting diodes (QD-LEDs) was investigated. Conventional long-chained oleic acid (OA) and trioctylphosphine (TOP) capping ligands were partially replaced by short-chained benzenethiol ligands in order to increase the stability of QDs during purification and also improve the electroluminescence performance of QD-LEDs. The quantum yield of the QD solution was increased from 41% to 84% by the benzenethiol ligand exchange. The mobility of the QD films with benzenethiol ligands approximately doubled to 2.42 × 10 −5 cm 2 V −1 s −1 from 1.19 × 10 −5 cm 2 V −1 s −1 compared to the device consisting of OA/TOP-capped QDs, and an approximately 1.8-fold improvement was achieved over QD-LEDs fabricated with bezenethiol ligand-exchanged QDs with respect to the maximum luminance and current efficiency. The turn-on voltage decreased by about −0.6 V through shifting the energy level of the QDs with benzenethiol ligands compared to conventional OA and TOP ligands.